#### Answer

$x=\left\{ -2i\sqrt{3},2i\sqrt{3} \right\}$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To find the nonreal complex solutions of the given equation, $
x^2=-12
,$ take the square root of both sides (Square Root Property). Then use the properties of radicals and use $i=\sqrt{-1}.$ Finally, simplify the radical.
$\bf{\text{Solution Details:}}$
Taking the square root of both sides (Square Root Property), the equation above is equivalent to
\begin{array}{l}\require{cancel}
x=\pm\sqrt{-12}
.\end{array}
Using the Product Rule of radicals which is given by $\sqrt[m]{x}\cdot\sqrt[m]{y}=\sqrt[m]{xy},$ the equation above is equivalent to\begin{array}{l}\require{cancel}
x=\pm\sqrt{-1}\cdot\sqrt{12}
.\end{array}
Using $i=\sqrt{-1},$ the equation above is equivalent to
\begin{array}{l}\require{cancel}
x=\pm i\sqrt{12}
.\end{array}
Writing the radicand as an expression that contains a factor that is a perfect power of the given index and then extracting the root of that factor, the equation above is equivalent to
\begin{array}{l}\require{cancel}
x=\pm i\sqrt{4\cdot3}
\\\\
x=\pm i\sqrt{(2)^2\cdot3}
\\\\
x=\pm i(2)\sqrt{3}
\\\\
x=\pm 2i\sqrt{3}
.\end{array}
Hence, $
x=\left\{ -2i\sqrt{3},2i\sqrt{3} \right\}
.$